The Use of Database Management Systems Using the Financial Accounting Cycle - Restu Alpiansah; Nur Fitriyah; Bambang Bambang; Mariusz Lewandowski (Pusat Riset dan Inovasi Nasional, 2025)
Accelerated technological progress has profoundly altered our lifestyles. The younger generation, as future leaders of the nation, must acquire digital skills to keep pace with technological progress. Adolescents of school age require essential instruction on digital literacy, especially with personal data management and academic requirements. Effective data management will enhance lifestyle efficiency and efficacy. This community service initiative sought to impart database administration proficiency through the financial accounting cycle framework to students at SMK Raudlatul Husna in Central Lombok Regency, West Nusa Tenggara. Thirty-two students engaged in the seminar and simulation activities. The activity was conducted through lectures and class tutorials on data storage methodologies in digital technologies, including Google Drive, Wordpress Web and Instagram. At the conclusion of the session, participants were queried regarding the activity summary, and the majority responded accurately and effectively. This activity is anticipated to be sustained continuously, enabling high school students to acquire both theoretical and practical information applicable to their daily lives.